Adenoid cystic carcinoma of the breast – an aggressive presentation with pulmonary, kidney, and brain metastases: a case report - Hasnae Alaoui Mhamdi; Hampig Raphael Kourie; Christiane Jungels; Philippe Aftimos; Rhizlane Belbaraka; Martine Piccart-Gebhart (Journal of Medical Case Reports, 2017)
Abstract Background Adenoid cystic carcinoma of the breast is a rare malignant neoplasm associated with an excellent prognosis and a very rare occurrence of metastases. Case presentation We report the case of an aggressive presentation in a 65-year-old woman, of Belgian origin, who was diagnosed as having adenoid cystic carcinoma of the breast and developed metastases to her lung, kidney, and brain. Conclusions We describe similar cases reported in the literature and discuss the molecular characteristics and treatment paradigm of this controversially aggressive disease entity.